Penerapan Metode Al-Iktisyaf dalam meningkatkan keterampilan membaca Kitab Kuning - Aini, Cicik (Prodi. Pendidikan Bahasa Arab, 2024)
The ability to read the classical book is very useful for understanding it, especially Fathul Qorib with the aim of knowing Islamic laws, especially fiqh laws, accompanied by the use of appropriate methods. This research aims to know iktisyaf method implementation to improve the reading proficiency of the Fathul Qarib in beginner level students and to know the inhibiting and supporting factors in using this method. For this purpose, the researcher uses qualitative research. For collecting data, the researcher used three methods there are interview, observation, and documentation. The objects studied in this research consist of students, teachers and school principals. For the data analysis technique used the Miles and Huberman model, starting from collecting data, presenting, and concluding.The results of this study shows that the implementation of iktisyaf method in improving the reading skill of Fathul Qarib consists of three steps, they are planning, implementation and evaluation. The supporting factors for implementing this method are the availability of the required learning media, increasing practice and reading the material and arguments with songs, while the inhibiting factors consists of the lack of enthusiasm and seriousness of students, the lack of teaching staff and lack of discipline